The expression of the interior decoration in the traditional mosques in Malacca: a critical review in relation to Islamic arts / Norzalifa Zainal Abidin - Zainal Abidin, Norzalifa (2004)
This study is to assess whether the application of decoration in the traditional mosques are truly successful in emanating their true roles as perceived in Islam and whether the hidden function and their true roles are truly achieved. The overall View of ISLAM, Islamic Arts in relation to decoration, the importance of mosque as a place of worship to Allah, and as an important building in the Muslim world are discussed. The concept of ‘Tawhid’ as the doctrine in Islam; and the way Islam perceives Beauty in its decorative arts as a mean of contemplation and Remembering Allah are elaborated. In order to understand these hidden functions and messages, the overall approach, roles, functions and typologies of decoration are explained. The uniqueness of Islamic Arts’ characteristics, roles, meanings and principles are governed universally by the Islamic doctrine — ‘Tawhid’ which expressed Oneness and Unity towards Contemplation to the One God — Allah. By looking at these aspects, one can truly assess whether the current usage of decorative motifs in mosque is in full success or not. A cross-reference of these usages is established with the true roles and functions of these decoration motifs as decoration in relation to Islamic Art as a whole. Successful applications of the interior decorative motifs can then be established and recommended for future applications. It is the intention of the study to be as an impetus for other broader and more critical analyses which can be made by others to fully comprehend the underlying concepts of the decorative motifs in the mosque interiors. This study is not an archetypal presentation of facts. A base reference study was made onto the oldest traditional mosque in the South East Asia region- Masjid Agung Demak in Central Java, Indonesia. Field studies were made to cover three selected traditional mosques in Malacca: Masjid Kampung Hulu, Masjid Tengkera and Masjid Al Azim. These mosques were chosen based on their built age — on two separate eras — the old traditional mosques: Masjid Kampung Hulu and Masjid Tengkera, have been built since the 18th Century and been treated as community mosques. These mosques are still in use, well maintained and conserved. The new traditional mosque, Masjid Al Azim is of the 20th Century, is a new and larger scale mosque, treated as the State Mosque in Malacca. Surveys were done to record and identify the decorative motifs in these mosques and to evaluate the users’ awareness and the effectiveness of these decoration. The aesthetic criteria of the decoration elements which have profound impacts onto the users are also identified. Furthermore, a close examination and analysis regarding certain aspects of the physical characteristics of the decorative motifs are presented.